Sodium, Magnesium, Calcium, Manganese, Iron, Copper, and Zinc in Serums of Beta Thalassemia Major Patients - Sahin, Ayse; Er, Elif Ozturk; Oz, Ersoy; Yildirmak, Zeynep Yildiz; Bakirdere, Sezgin (SPRINGERNATURE, 2021)
Thalassemia major is the most severe form of thalassemia and occurs with the impaired synthesis of beta-globin which causes the accumulation of unpaired alpha globin chain. Patients with beta thalassemia major can only survive with periodically safe blood transfusions leading to the accumulation of iron in the bloods of patients, and this causes several endocrinopathies. Although iron overload in thalassemic patients has been extensively studied, there is little information about the levels of other trace elements. The aim of this study was to investigate the differences of serum concentrations of sodium, magnesium, calcium, manganese, iron, copper, and zinc for patients with major beta-thalassemia. Concentration of elements was determined by inductively coupled plasma-mass spectrometry system. The statistical difference between the elemental concentrations of the patient and control groups was found by the Mann-WhitneyUtest. In addition, the relationship between concentrations of the measured elements for each group was determined by the Spearman correlation test. The results revealed that iron, zinc, magnesium, and manganese serum levels of thalassemic patients were significantly higher than the control group while calcium concentration was statistically lower than the control group. There was no significant difference observed for copper and sodium levels of patients when compared to the healthy control group.
Keywords: Beta thalassemia major; Trace elements; Serum samples; Statistical test; DIABETES-MELLITUS; TRACE-ELEMENTS; ICP-MS; METABOLISM; OVERLOAD; PATHOPHYSIOLOGY; CARDIOMYOPATHY; DEFICIENCY; PHYSIOLOGY; SAMPLES; Biochemistry & Molecular Biology; Endocrinology & Metabolism